2015
DOI: 10.1017/s0950268814003628
|View full text |Cite
|
Sign up to set email alerts
|

A norovirus oyster-related outbreak in a nursing home in France, January 2012

Abstract: The presence of norovirus in shellfish is a public health concern in Europe. Here, we report the results of an investigation into a norovirus gastroenteritis outbreak following a festive lunch which affected 84 (57%) residents and staff members of a nursing home in January 2012 in France. Individuals who had eaten oysters had a significantly higher risk of developing symptoms in the following 2·5 days than those who had not, the risk increasing with the amount eaten [relative risk 2·2 (1·0-4·6) and 3·3 (1·6-6·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 25 publications
2
16
0
1
Order By: Relevance
“…These outbreak settings have likewise been identified in other Asia countries, such as Japan and South Korea (18,20), as the most common settings for norovirus outbreaks. In contrast, in the United States and Europe, healthcare facilities (primarily nursing homes and hospitals) are the most commonly reported setting for norovirus outbreaks (11,21,22). The high proportion of norovirus outbreaks in childcare centers and schools seems unique to China and might be associated with the high population density in these settings (23) and the enhanced monitoring and reporting of any outbreaks in schools in China.…”
Section: Discussionmentioning
confidence: 99%
“…These outbreak settings have likewise been identified in other Asia countries, such as Japan and South Korea (18,20), as the most common settings for norovirus outbreaks. In contrast, in the United States and Europe, healthcare facilities (primarily nursing homes and hospitals) are the most commonly reported setting for norovirus outbreaks (11,21,22). The high proportion of norovirus outbreaks in childcare centers and schools seems unique to China and might be associated with the high population density in these settings (23) and the enhanced monitoring and reporting of any outbreaks in schools in China.…”
Section: Discussionmentioning
confidence: 99%
“…Shellfish hygiene regulations currently do not include virus contamination. However, viruses such as NoV and Hepatitis A (HAV) have been detected in shellfish (Polo et al 2015), which were implicated in NoV and HAV outbreaks (Loury et al 2015). To ensure protection of shellfish waters, the introduction of virus testing methods or viral standards has been proposed to improve viral hygiene with respect to shellfish production, and is discussed below (EURL 2014a).…”
Section: Regulating Nov In Shellfish Waters and Shellfish: Current Prmentioning
confidence: 99%
“…Human enteric viruses have been reported to be among the main causative agents associated with bivalve mollusk outbreaks. HuNoV and HAV account for the majority of these shellfish outbreaks (2,(5)(6)(7)(8). Pioneering studies have shown that these enteric viruses persist and can bioaccumulate to high titers within shellfish tissues (9-12).…”
mentioning
confidence: 99%